Fusarium solani infection disrupts metabolism during the germination of roselle (Hibiscus sabdariffa L.) seeds - Tahmasebi, Aminallah; Roach, Thomas; Shin, Song Yub; Lee, Chul Won (Frontiers in Plant Science, 2023)
Fungal infections adversely influence the production and quality of seeds. Previously, we reported Fusarium solani was reported as the causal agent of roselle (Hibiscus sabdariffa L.) seed rot. Here, we evaluated the information on relationship between seed metabolism and F. solani infection is lacking, and accordingly this study was planned to evaluate the effect of F. solani infection on the germination, biochemical composition, energy reserves and antioxidant activity of roselle seeds. The results showed that roselle seeds infected with F. solani had reduced total germination by ca. 55%. Additionally, the fungal infection decreased antioxidant activity, total phenolic content, protein, sugar (sucrose, fructose and glucose) and some amino acid (glutamine, serine, and arginine) contents. In contrast, some metabolites were more abundant in infected seeds, including alanine (2.1-fold) and some fatty acids (palmitic acid and heptadecanoic acid by 1.1-fold and 1.4-fold, respectively). The infection-associated changes in fatty acid profile resulted in the ratio of unsaturated: saturated fatty acids being 2.1-fold higher in infected seeds. Therefore, our results reveal that F. solani infection remarkably altered the biochemical composition of roselle seeds, which may have contributed to the loss of germination and quality of roselle seeds.